Fertilização com bioativo composto em cana-de-açúcar de terceiro corte - MARIELE SILVA ABREU (2022)
The cultivation of sugarcane (Saccharum spp.) in brazil is one of the most important, due to the vast area occupied in the production regions. However, for the good performance of the culture, mainly in soils with low fertility and low content of organic matter, the use of fertilization is necessary. Fertilizers with a high content of bioactive compounds, in addition to improving the physicochemical and biological conditions of the soil, promote adequate nutritional balance in crops, reducing dependence on the use of mineral fertilizers. Therefore, the objective of this work was to evaluate the effect of the use of organomineral fertilizer and filter cake, in the development of sugarcane from the production capacity, to the technological quality of this input, correlating with the change in the biochemical patterns of the ground. The experimental design used was in randomized blocks, with nine treatments and four replications. The treatments consisted of T1 - control, T2 - standard mixture dose 100% (mixture of filter cake + mineral fertilizer), T3 - standard mixture 50%, T4 - bac 100% (bioactive compound superbac®), T5 - bac 50% , T6 – standard blend 50% + bac 50%, T7 – standard blend 70% + bac 30%, T8 – standard blend 80% + bac 20%, T9 – standard blend 90% + bac 10%. Productive parameters (number of tillers at 30, 60 and 90 days, at harvest time, stalk weight and tons of stalk per hectare) and technological parameters (BRIX, POL, PCC, ART, ATR and AR) were evaluated. Of plants harvested in the useful area of each plot, soil samples for microbiological and chemical analysis were also carried out after the harvest. The treatments where the fertilizations with the organomineral occurred provided the highest averages for some production parameters. There was an effect on the initial development of the crop, on the number of tillers, stalk productivity and on the increase in the levels of reducing sugars when using the fertilizer, alone or associated with the standard management performed by the plant. It was concluded that the organomineral fertilizer and its combinations provided increases in the tons of stalk per hectare and in the increase in the levels of reducing sugars.